The Role of Institutions of Higher Education in Preparing Students to Write in the Workplace: Suggestions for Writing Curricula and Pedagogy - Hodgman, Matthew R. (Journal of Education and Training, 2023)
Employers have expressed discontent with the workplace skill sets and overall professionalism of recent college graduates. Employers specifically report that graduates lack important work-related writing skills such as editing, research, and data analysis skills. The literature continually provides metrics on recent graduates’ weaknesses as workplace writers. If graduates are to maximize their marketability to employers, perceived writing gaps must be addressed specifically in the context of higher education writing curricula and pedagogy. Based on employer reports on the specific writing skill sets lacking in recent college graduates, this article is a primer on the topic of meeting employers’ workplace writing needs and puts forth (1) the context behind and causes of a workplace writing skills gap in recent college graduates, (2) curricular and pedagogical suggestions for institutions of higher education (IHEs) to strengthen work-related writing competencies in college students, and (3) recommendations for future research pertaining to meeting the writing needs of the workplace.